2008
DOI: 10.2514/1.33428
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Response Structural Optimization of a Joined Wing Using Equivalent Loads

Abstract: Public reporting burden for the collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden, to Washington Headquarters Services, Directorate for Information Operations and R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 21 publications
0
26
0
Order By: Relevance
“…Typical joined-wing configurations (Wolkovitch, 1986;Chambers, 2005) are characterized by significant structural geometric nonlinearities (Blair et al, 2005;Kim et al, 2008;Liu et al, 2010). As a consequence, preliminary design complexity is increased (Blair et al, 2005): existing procedures successfully adopted by the aerospace industry rely mainly on linear tools not able to correctly reproduce these effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Typical joined-wing configurations (Wolkovitch, 1986;Chambers, 2005) are characterized by significant structural geometric nonlinearities (Blair et al, 2005;Kim et al, 2008;Liu et al, 2010). As a consequence, preliminary design complexity is increased (Blair et al, 2005): existing procedures successfully adopted by the aerospace industry rely mainly on linear tools not able to correctly reproduce these effects.…”
Section: Introductionmentioning
confidence: 99%
“…What has proven to be very effective in the past for classical cantilevered configurations, then, cannot (Kim et al, 2008) be directly translated into procedures that have the same degree of computational efficiency and accuracy, when Joined Wings are considered (Weisshaar and Lee, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The process is iterated until convergence. The ESL methodology was originally developed and applied to the joinedwing application by Lee et al 10 Kim et al 11 showed that ESL optimization produced a better design than a fully stressed design methodology for a detailed joined wing case. Kim et al 12 later showed that the ESL methodology produced the same joined-wing design as a conventional gradient based optimization, but at a much lower cost.…”
Section: Discussionmentioning
confidence: 99%
“…There is therefore a need to develop a method of the structure optimization taking structural nonlinearity into account. The NROEL method [4,5,6] could be an example. This is a modified gradient method, which transforms the nonlinear problem to the linear one and then solves it.…”
Section: Introductionmentioning
confidence: 99%